Sikap Konsumen Terhadap Barang-Barang Gray Market - Prakosa, Yusuf Dwi; Anwar, Misbahul (Jurnal Manajemen Bisnis, 2017)
This study aims to to analyze the influence of price consciousness, price-quality inference, risk averseness to attitude and purchase intentions on goods gray market. The study sample are students 8 University in Daerah Istimewa Yogyakarta who know the differences between goods gray market with those who are not goods gray market. The kind of research this is research survey by distributing the questionnaire to 160 respondents determined by using a method of non probability of sampling with a kind of purposive sampling. Instrument analysis using Structural Equation Modeling with the program AMOS 22. Price consciousness has a significant positive effect on attitude. Price-quality inference has a significant negative effect on attitude. Risk averseness has a significant negative effect on attitude. Attitude have a significant positive effect on purchase intentions. Price consciousness has a significant positive effect on purchase intentions. Price-quality inference has no significant effect on purchase intention. Risk averseness has no significant effect on purchasing intentions. Price consciousness has a significant positive effect on purchase intentions through attitude. Price-quality inference has no significant effect on purchase intentions through attitude. Risk averseness has no significant effect on purchase intentions through attitudes.